Linking eroded upland corn productivity to household income-expenditure and food nutrient intakes of children - Tugay, Ronaldo E. Jr.; Alviola, Pedro A. IV. (Davao City School of Management, University of the Philippines Mindanao, 2016)
Climate change continue to affect the livelihood of farmers. Pressure continue to increase in agricultural production due to higher erosion rates brought by climate change. Upland corn production is especially vulnerable. The estimation of the Cobb Douglas Production Function showed that erosion decreases upland corn yields. T-tests on farm profitability, household income-expenditures, and food nutrient intakes of children were done. Farm profits were lesser in severe erosion compared to moderate erosion. Farming income was greater in moderate erosion while non-farming income was greater in severe erosion. There was no difference in expenditure except for expenditure in fruits, vegetables, and meat. Food and Nutrient intakes of children were greater for households in severe erosion. Conclusively, non-farming employment and market access mitigated the possible effects of soil-erosion to the farm households. Non-farming activities provided stable income while better market access led to accessibility to certain foods.
Thesis (BS Agribusiness Economics)-- University of the Philippines Mindanao, June 2016